Variation in general practitioners' information-seeking behaviour - a cross-sectional study on the influence of gender, age and practice form - Jette V. Le; Line B. Pedersen; Helle Riisgaard; Jesper Lykkegaard; Jørgen Nexøe; Jeanette Lemmergaard; Jens Søndergaard (Taylor & Francis Group, 2016)
Objective: To assess general practitioners' (GPs') information-seeking behaviour and perceived importance of sources of scientific medical information and to investigate associations with GP characteristics. Design: A national cross-sectional survey was distributed electronically in December 2013. Setting: Danish general practice. Subjects: A population of 3440 GPs (corresponding to approximately 96% of all Danish GPs). Main outcome measures: GPs' use and perceived importance of information sources. Multilevel mixed-effects logit models were used to investigate associations with GP characteristics after adjusting for relevant covariates. Results: A total of 1580 GPs (46.4%) responded to the questionnaire. GPs' information-seeking behaviour is associated with gender, age and practice form. Single-handed GPs use their colleagues as an information source significantly less than GPs working in partnership practices and they do not use other sources more frequently. Compared with their younger colleagues, GPs aged above 44 years are less likely to seek information from colleagues, guidelines and websites, but more likely to seek information from medical journals. Male and female GPs seek information equally frequently. However, whereas male GPs are more likely than female GPs to find that pharmaceutical sales representative and non-refundable CME meetings are important, they are less likely to find that colleagues, refundable CME meetings, guidelines and websites are important. Conclusion: Results from this study indicate that GP characteristics should be taken into consideration when disseminating scientific medical information, to ensure that patients receive medically updated, high-quality care.KEY POINTS Research indicates that information-seeking behaviour is associated with GP characteristics. Further insights could provide opportunities for targeting information dissemination strategies. Single-handed GPs seek information from colleagues less frequently than GPs in partnerships and do not use other sources more frequently. GPs aged above 44 years do not seek information as frequently as their younger colleagues and prefer other information sources. Male and female GPs seek information equally frequently, but do not consider information sources equally important in keeping medically updated.